What is the physiological time to recovery after concussion? A systematic review. Issue 12 (28th April 2017) - Kamins, Joshua; Bigler, Erin; Covassin, Tracey; Henry, Luke; Kemp, Simon; Leddy, John J; Mayer, Andrew; McCrea, Michael; Prins, Mayumi; Schneider, Kathryn J; Valovich McLeod, Tamara C; Zemek, Roger; et al.
Abstract : Aim or objective: The aim of this study is to consolidate studies of physiological measures following sport-related concussion (SRC) to determine if a time course of postinjury altered neurobiology can be outlined. This biological time course was considered with respect to clinically relevant outcomes such as vulnerability to repeat injury and safe timing of return to physical contact risk. Design: Systematic review. Data sources: PubMed, CINAHL, Cochrane Central, PsychINFO. Eligibility criteria for selecting studies: Studies were included if they reported original research on physiological or neurobiological changes after SRC. Excluded were cases series <5 subjects, reviews, meta-analyses, editorials, animal research and research not pertaining to SRC. Results: A total of 5834 articles were identified, of which 80 were included for full-text data extraction and review. Relatively few longitudinal studies exist that follow both physiological dysfunction and clinical measures to recovery. Summary/conclusions: Modalities of measuring physiological change after SRC were categorised into the following: functional MRI, diffusion tensor imaging, magnetic resonance spectroscopy, cerebral blood flow, electrophysiology, heart rate, exercise, fluid biomarkers and transcranial magnetic stimulation. Due to differences in modalities, time course, study design and outcomes, it is not possible to define a single 'physiological time window' for SRC recovery. Multiple studies suggest physiological dysfunction may outlast current clinical measures of recovery, supporting a buffer zone of gradually increasing activity before full contact risk. Future studies need to use generalisable populations, longitudinal designs following to physiological and clinical recovery and careful correlation of neurobiological modalities with clinical measures.